Does optimising the business environment enhance enterprise resilience? The role of digital innovation and entrepreneurial spirit - Ruonan Wang; Guangsheng Zhang (Humanities & Social Sciences Communications)
Abstract In an era marked by escalating uncertainty in the external environment, enhancing enterprise resilience is a top research priority. Although the business environment exerts a considerable influence on enterprise activities, the academic community has paid scant attention to how it impacts enterprise resilience. Based on the data of China’s urban business environment and sample data of listed companies from 2013 to 2021, this study examined the long-term value of the business environment from the perspective of enterprise resilience and explores its underlying mechanisms. It found that the business environment is crucial in improving the enterprise resilience. The human resource, financial, market and innovation environments are the main factors that contribute to enterprise resilience. Mechanism tests revealed that the business environment fosters enterprise resilience by propelling digital innovation. Furthermore, entrepreneurial spirit can amplify the positive effects of the business environment on digital innovation, thereby strengthening enterprise resilience. Heterogeneity analysis suggested that upgrading the business environment exhibits a more salient improvement in resilience for private enterprises, small and medium-sized enterprises and high-tech industries compared to state-owned, large-sized and traditional industries. This study investigates the important theoretical and practical value of understanding how to enhance enterprise resilience through optimising the business environment, driving digital innovation and fostering entrepreneurial spirit.